2019
DOI: 10.1055/s-0039-3400966
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Pregnancy: Evidence for Major Roles by the Uterine and Placental Kisspeptin/KISS1R Signaling Systems

Abstract: Several studies provide strong evidence suggesting that in addition to central kisspeptin/KISS1R signaling, the peripheral uterine- and placental-based kisspeptin/KISS1R signaling systems are major regulators of pregnancy. Specifically, the evidence suggests that the uterine-based system regulates embryo implantation and decidualization, while both the uterine- and placental-based systems regulate placentation. Uterine kisspeptin and KISS1R regulate embryo implantation by controlling the availability of endome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 100 publications
(130 reference statements)
0
11
0
Order By: Relevance
“…This indicates a potential role of kisspeptin in the preparation of endometrial tissue for implantation. Kisspeptin knockout mice exhibit thin, weak uteri with almost no endometrial glands, suggesting kisspeptin is an important regulator of normal endometrial development [34]. Kisspeptin may also act as a mediator that facilitates implantation of the growing embryo to the uterine wall.…”
Section: Kisspeptin In the Luteal Phase And Implantationmentioning
confidence: 99%
See 3 more Smart Citations
“…This indicates a potential role of kisspeptin in the preparation of endometrial tissue for implantation. Kisspeptin knockout mice exhibit thin, weak uteri with almost no endometrial glands, suggesting kisspeptin is an important regulator of normal endometrial development [34]. Kisspeptin may also act as a mediator that facilitates implantation of the growing embryo to the uterine wall.…”
Section: Kisspeptin In the Luteal Phase And Implantationmentioning
confidence: 99%
“…Kisspeptin may also act as a mediator that facilitates implantation of the growing embryo to the uterine wall. It has been shown that exogenous kisspeptin administration strengthens adhesion of kisspeptin-expressing trophoblast cells to collagen present in uterine tissue [34]. Immediately after implantation, kisspeptin levels are known to rise; this suggests involvement of kisspeptin during the decidualization process [35].…”
Section: Kisspeptin In the Luteal Phase And Implantationmentioning
confidence: 99%
See 2 more Smart Citations
“…LGR4 couples to Ga s (and thereby stimulates adenylyl cyclase activity and cAMP formation), LPAR3 couples to Ga q/11 (and thereby stimulates phospholipase C activity and diacyl glycerol formation and Ca 2þ mobilization) and Ga i/0 inhibits adenylyl cyclase activity (10), whereas KISS1R couples to Ga q/11 (10,11). Deletion of these receptors in the mouse revealed critical roles for GPCRs in the acquisition of uterine receptivity, embryo implantation, and/or endometrial decidualization (3)(4)(5)(6)(7)12).…”
mentioning
confidence: 99%